Generalized Archimedean spaces and expansivity - Metzger R. (2021)
RM was partially supported by Fondecyt-Concytec contract 100-2018 , HV was partially supported by Universidad Nacional de Ingeniería FC-PF-33-2021 and P-CC-2021-000666 . CAM was partially supported by CNPq -Brazil and the NRF Brain Pool Grant funded by the Korea government (No. 2020H1D3A2A01085417 ).